ESTUDIOS SOBRE LA MEDULA HUESOSA V TIPOS CELULARES Y ESQUEMAS EVOLUTIVOS EN LA MEDULA DE LA RATA BLANCA - GONZALEZ GUZMAN, IGNACIO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
Changes in the chromopexy and the proliferative capacity of the reticulo-endothelial systems, formation of antibodies, and the cellular enzyme dynamics are considered in relation to leprosy Rejuvenation of histiocytes, increase in lipolytic enzymes, an
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, MEDULA, HUESOSA, CELULARES, ESQUEMAS, EVOLUTIVOS, MEDULA, RATA; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA VETERINARIA